Factors Affecting the Quality of Medical Record Services - Kasim, Felix (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Medical records play a crucial role in supporting safe, high-quality, and continuous healthcare services. However, the quality of medical record services at many healthcare facilities, including Granmed Hospital Lubuk Pakam, still faces various challenges.Objective:This study aims to analyze the factors affecting the quality of medical record services, including individual factors (knowledge, perception, workload), organizational factors (policies, training, supervision), and technological factors (facilities and infrastructure). Research Methods: A quantitative analytic observational study with a cross-sectional design was conducted. A total of 75 healthcare and administrative workers involved in medical record management were selected using total sampling. Data were collected through structured questionnaires and medical record audits, then analyzed using chi-square tests and multiple logistic regression. Results: There were significant relationships between knowledge (p=0.002), workload (p=0.015), training and supervision (p=0.049), and availability of facilities and infrastructure (p=0.022) with the quality of medical record services. Most respondents reported a heavy workload and inadequate facilities.Conclusion:Knowledge, workload, training-supervision, and facility availability significantly influence the quality of medical record services. Efforts to strengthen human resources, manage workloads better, enhance supervision, and improve infrastructure are essential to enhance the quality of medical record documentation.